(untitled) (Research Nepal Journal of Development Studies, 2025)
Tourism cooperatives in Nepal represent an emerging model of community-based economic organization that integrates cooperative principles with sustainable tourism development through micro credit mobilization on community mobilization. These institutions have the potential to empower local communities, enhance equitable benefit distribution, and promote inclusive tourism practices. However, despite their promise, tourism cooperatives face numerous structural, institutional, and operational challenges. This study critically examines the opportunities and challenges of tourism cooperatives in Nepal through a qualitative review of existing literature on cooperatives, rural tourism, and sustainable tourism development. The findings reveal that while tourism cooperatives can foster financial inclusion, community participation, and cultural preservation, they are constrained by weak governance, limited access to capital, inadequate professional management, and policy inconsistencies. The study argues that strengthening institutional frameworks, enhancing capacity building, and promoting collaborative governance are essential to unlocking the full potential of tourism cooperatives. The paper contributes to the growing discourse on community-based tourism and cooperative development in Nepal and offers policy recommendations for sustainable and inclusive tourism growth in community empowerment financially.